Comparison of Magnetic Flux Density for Six-Phase and Three-Phase Induction Motor using COMSOL Multiphysics - Faeq, Dastan Tofiq; Raafat, Jwan Satei; Ali, Mohammed Moanes E. (Sulaimani Journal for Pure and Applied Sciences, 2019)
The basic design of induction motors has not changed in the last years, with latest and good insulation materials, pre-simulation for design, computer optimization techniques in design and using automated manufacturing devices have resulted in motors of less cost per kW, heating reduction and smaller physical size. Due to standards by International of physical dimensions and frame sizes the motors from most manufacturers are physically interchangeable and they have similar performance characteristics, dimensions and electrical distribution of multiphase coils are affecting on magnetic field density, because of difficulty in measuring magnetic flux in each point of the machine computer simulations help in machine design to demonstrate and adjustments in magnetic flux distribution. Three-phase and six-phase induction motor electromagnetic models are developed in two-dimensions in the finite element method based software-tool Computer Solutions (COMSOL) Multiphysics. Frequency domain simulation result obtained magnetic field density comparison between three phase and six phase induction motors.
Keywords: Induction Motor; Flux Density; Simulation